(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
In 2013, the Uruguayan Parliament passed Law No. 19122: Afro-descendants Regulations to promote their participation in the areas of education and work, which has been regulated by the Executive. This law provides affirmative action to favour Afro-descendants and recognise their contributions to national culture and identity. It introduces redistribution and recognition; demands that have been claimed for at least three decades by the organisations of the Uruguayan Afro-descendants’ movement. This work presents the main results of interviews and discussion groups about the implementation of the aforementioned law.